Perancangan Kapal Tanpa Awak Dengan Pengendali Otomatis dan Kontrol Jarak Jauh - Samidun, Samidun; Sudarsono, Sudarsono; Endriatno, Nanang (Teknik Mesin Universitas Halu Oleo, 2023)
The development of science and technology in the maritime field is increasing marked by the rapid progress that occurs with the creation of increasingly sophisticated equipment. However, the development of unmanned ship technology is still not widely applied in Indonesia, so it is necessary to develop further technology on unmanned ship technology so that it can be applied in Indonesia, both in the military, commercial and so on. For that we designed an unmanned ship without a remote control automatic control. In this remote control automatic ship program, there are two main programs, namely the transmitter/sender program, where this program is used to program the remote control, while the receiver/receiver program is used on the ship to be steered, and to connect the transmitter and receiver. using the nRF25L01 module. The workings of this tool is that when potentiometer 1 is read it will move the servo motor, and if potentiometer 2 is read, it will move the Brushed Motor through the ESC. The comparison results at an angle of 45°, the track diameter is 145.33 cm, with a time of 5.59 seconds and a speed of 26.02 cm/s. At an angle of 30°, the track diameter is 226.67 cm, with a time of 9.51 seconds and a speed of 23.80 cm/s. While at an angle of 15°, the track diameter is 331.33 cm, with a time of 15.52 seconds and a speed of 21.36 cm/s.Keywords: Unmanned Ship, nRF24L01, Potentiometer